2008
DOI: 10.1016/j.yqres.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Sand dunes as a major proximal dust source for late Pleistocene loess in the Negev Desert, Israel

Abstract: Grain size analyses of three hilltop, primary eolian loess sequences in the Negev desert, southern Israel, show a bimodal grain-size distribution at 50–60 μm and 3–8 μm. Using analyses of mineralogy and OSL ages we demonstrate that the coarse mode is composed mostly of quartz grains and its relative magnitude increases regionally with time, suggesting an enhancement of a time-transgressive proximal dust source compared to a distal, Saharan fine-grain dust. The only proximal dust source for large amount of coar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
193
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(202 citation statements)
references
References 46 publications
9
193
0
Order By: Relevance
“…Furthermore, because these calculated accretion rates are of primary loess, we can explain their change over time directly in terms of change in dust sources, availability and transport. In this carbonate terrain, Crouvi et al [2008] showed that the Figure 8. Carbonate-free particle size distribution of the three loess units from Mount Harif sequence showing bimodality [Crouvi et al, 2008].…”
Section: Negev Loess Chronology and Dust Accretion Ratesmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, because these calculated accretion rates are of primary loess, we can explain their change over time directly in terms of change in dust sources, availability and transport. In this carbonate terrain, Crouvi et al [2008] showed that the Figure 8. Carbonate-free particle size distribution of the three loess units from Mount Harif sequence showing bimodality [Crouvi et al, 2008].…”
Section: Negev Loess Chronology and Dust Accretion Ratesmentioning
confidence: 97%
“…The suggested proximal sources are Wadi El-Arish in northern Sinai [Yaalon, 1971[Yaalon, , 1987Yaalon and Ganor, 1973;Yaalon and Dan, 1974;Ganor et al, 1991], the Mediterranean shelf exposed during periods of low sea level [Gerson and Amit, 1987;Crouvi et al, 2008;Enzel et al, 2008] and sand dunes that advanced into the Sinai and Negev during the late Pleistocene [Crouvi et al, 2008].…”
Section: Loess In the Negev Desertmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many significant studies of desert loess; the idea has been discussed for many years (see in particular Butler(1956), Wright(2006) Smalley and Krinsley (1978), Tsoar and Pye (1987), Crouvi et al (2008Crouvi et al ( , 2012. There is, underpinning the discussion on the nature and distribution of desert loess, the question of the origin of the material.…”
Section: Desert Loessmentioning
confidence: 99%
“…It can be lifted from desert regions and transported vast distances at great heights. Various particle production mechanisms are involved (Smalley et al 2005, O'Hara-Dhand et al 2010, Crouvi et al 2008). …”
Section: Desert Loessmentioning
confidence: 99%